การศึกษาการดำเนินงานนิเทศภายในของโรงเรียนราชินี - เทียนวรรณ นันทิยา; สุดรุ่ง ผศ.ดร.จุไรรัตน์ (An Online Journal of Education, 2015)
การวิจัยในครั้งนี้ มีวัตถุประสงค์เพื่อศึกษาการดำเนินงานนิเทศภายในของโรงเรียนราชินี ประชากรในการวิจัยในครั้งนี้ได้แก่ คณะกรรมการนิเทศภายในโรงเรียนและผู้นิเทศ รวมทั้งหมดจำนวน 60 คน เครื่องมือที่ใช้เป็นแบบสอบถาม มีลักษณะเป็นแบบตรวจสอบรายการและแบบปลายเปิด วิเคราะห์ข้อมูลโดยการแจกแจงความถี่ และหาค่าร้อยละ ผลวิจัยพบว่า 1) ด้านการวางแผนการนิเทศภายใน พบว่า การสำรวจสภาพปัจจุบัน ปัญหาและความจำเป็นในการจัดนิเทศภายใน ศึกษาจากปัญหาการปฏิบัติงานของครูในโรงเรียน โดยได้มอบหมายให้หัวหน้ากลุ่มสาระการเรียนรู้เป็นผู้ดำเนินการ มีการจัดลำดับความสำคัญของข้อมูลให้สอดคล้องกับนโยบายต้นสังกัด พิจารณาจากความเป็นไปได้ใน การแก้ปัญหา การจัดตั้งคณะกรรมการดำเนินงานนิเทศภายในผู้บริหารเป็นผู้พิจารณาคุณสมบัติตามความเหมาะสม จากผู้มีตำแหน่งหน้าที่ตามสายงานบริหาร มีหน้าที่จัดทำโครงการนิเทศภายในโรงเรียน ให้สอดคล้องกับนโยบายของโรงเรียน มีการประชุมชี้แจงให้คณะกรรมการรับทราบเรื่องวิธีการดำเนินงานการจัดทำแผนงาน/โครงการนิเทศให้สอดคล้องกับนโยบายของโรงเรียนมีการกำหนดการปฏิบัติโครงการนิเทศภายในตามแผนงานของโรงเรียนและจัดทำโครงการนิเทศภายในช่วงปิดภาคเรียนที่ 2 2) ด้านการดำเนินการนิเทศภายในโรงเรียน พบว่า ผู้กำหนดกิจกรรม การนิเทศภายในคือรองผู้อำนวยการ และคณะกรรมการดำเนินงานนิเทศภายใน เกณฑ์ในการพิจารณากิจกรรมนิเทศ คือ สภาพความต้องการจำเป็นและปัญหาของโรงเรียน กิจกรรมการนิเทศที่โรงเรียนใช้คือ การสังเกตการสอนและการติดตามผลการดำเนินงานนิเทศภายใน โรงเรียนอำนวยความสะดวกในการเสนอโครงการและการจัดกิจกรรมการนิเทศ มีการส่งเสริมขวัญและกำลังใจแก่ผู้ปฏิบัติงานด้วยการสร้างบรรยากาศที่ดีในการปฏิบัติงาน 3) ด้านการประเมินผลนิเทศภายในโรงเรียน พบว่า โรงเรียนใช้วิธีการประเมินผลการปฏิบัติงาน โดยใช้แบบประเมินการปฏิบัติงาน ผู้รับผิดชอบคือรองผู้อำนวยการ และคณะกรรมการดำเนินงานนิเทศภายใน และได้นำผลการประเมินไปใช้ประโยชน์ในวางแผนพัฒนาการเรียนการสอน The purpose of this study was to study the operation of in-school supervision of Rajini School. The population consisted of in-school supervisory committees and supervisors in total of 60 persons. The research instrument was checklists, open-ended questionnaires. The data was analyzed by frequency and percentage. The survey findings were as follows: 1) The in-school supervision planning, the problems of teachers’ performances were examined in order to study of the current states, problems, and needs for the in-school supervision. This task was conducted by the head of departments to arranged the data according to significance with policy considered the possibility in solving the problems. Moreover, set the in-school supervisory committee by the administrators who considered qualifications of each committee from their duties. Then, they were responsible for conducting the in-school supervision in accordance with the school’s policy. Meetings were held to inform the committee about operating, planning the project in line with the school’s policy to the methods in planning/ implementing in line with the school’s policy, the in-school supervision was projected to be done within the second semester. 2) The operation of in-school supervision, the research revealed that in-school supervisory activities were managed by the deputy director of school and the in-school supervisory committee. The criteria in considering for the supervisory activities included the needs and problems occurred within the school. The in-school supervisory activities were teaching observation and operation monitoring. The school facilitated for presenting the project and organizing supervisory activities. 3) The evaluation of in-school supervision activities, the deputy director and in-school supervisory committee evaluated the performance by using assessment form to take the result for planning in teaching development.